Urban opportunities and conflicts around street musicians: the relationship between the configuration of public space and outdoor acoustics in Ciutat Vella, Barcelona. Issue 5 (2nd September 2020) - Clua, Álvaro; Llorca-Bofí, Josep; Psarra, Sophia
ABSTRACT: The practice of busking and street music performance is becoming key to the identity of cities. However, although the spatial configuration and acoustics of historic city centres are interrelated, few rigorous studies have been undertaken on this area. The paper presents the results of a quantitative and comparative analysis of the space syntax configuration and on-site sound recordings in four main open environments within the inner core of Barcelona. The aim of this work is to highlight the conflict points between outdoor acoustics and movement flows in order to inform future designs and management of those public spaces.